(untitled) (International Journal of Built Environment and Sustainability, 2018)
Dual formal and informal transport modes have been complementing one another in Bandung City for more than four decades now. The issue appears due to inability of formal transport to provide adequate services to the citizens. However, this accompaniment has brought Bandung City to a quasi-seamless transportation process as both transport modes play their roles as a continuum. Amid insufficient public transportation system in Bandung City, the informal transport modes have properly paired their formal transport counterparts. This study was conducted in Bandung City, Indonesia, by profiling the transportation users, observing the characteristics of both formal and informal transports, and acquiring the relevant secondary information at city and national levels. The study found that within the issue of appropriateness of few modes of informal transport such as becaks and ojeks, they have shown their contribution to the state of quasi-seamless transit process in the city as well as their impacts to reduce the CO2 emission in comparison to formal fossil fuel-based transportation.